The influence of being part of a tourist network on hotels' financial performance. (September 2019) - Rotondo, Federico; Fadda, Nicoletta
Highlights: Taking part in a tourist network has a positive effect on hotels' profitability. In particular, taking part in a tourist network has a positive effect on the profitability of the operating area. Taking part in a tourist network impacts on the dimensions of relationships, efficiency, quality and the volume of business. The positive effect on the profitability is related to the improvement of relationships that leads to increased efficiency. Abstract: In today's society, governance networks are increasingly seen as important tools for coping with complex problems or to achieve results of common interest. However, limited empirical evidence exists on whether networks really work and what advantages participants can gain from them. This paper aims to provide evidence of whether and why being part of a tourist network really improves the financial performance of hotels. An explanatory sequential mixed method, consisting of a quantitative analysis based on random effects method on a panel data for the 2010-2015 period for a sample of 124 Sardinian hotels, followed by a qualitative investigation on 26 of them, was used. The results reveal that taking part in a tourist network positively impacts on the profitability of the operating area of hotels, and this is mainly due to the improvement of relationships with community, competitors and customers. This has major implications for hotels and for destinations.